ROCK PHYSICS TEMPLATE TO ESTIMATE THE EFFECTS OF TOTAL ORGANIC CARBON (TOC) AND MINERALOGY ON THE SEISMIC ELASTIC PROPERTIES OF IMMATURE SHALE RESERVOIR - Harnanti Y Hutami; Tiara Larasati Priniarti; Ign Sonny Winardhi; Handoyo . (Testing Center for Oil and Gas LEMIGAS, 2019)
The low porosity and permeability shale are nowadays known as self-resourcing reservoirs. In the unique organic shales, TOC has a signifi cant contribution to the elastic properties of rocks. TOC behaves like porosity to a density log and effects in decreasing density. To reduce the uncertainty due to TOC and mineral variability effect, a quantitative interpretation of shale reservoirs should be done properly to obtain the best image of shale systems. In this study, we built rock-physics templates (RPT) to esti mate seismic response by defi ning the relationship between total organic carbon (TOC) and effective elastic properties of shale reservoirs of a data set from South Sumatera Basin, Indonesia. RPT is carried out by incorporating the amount of organic matter into shale pore space as a solid-fi lling inclusion. Moreover, shale porosity is assumed to be fully water-saturated determined by the in-situ conditions. We have estimated the general distribution of pore geometry by investigating aspect ratio from the dataset. A solid background of shale from several different minerals is estimated by using effective medium theory. Properties of porous rocks for solid pore infi ll are estimated from a generalization of Brown-Korringa Equation. Effective elastic properties of bulk rock frame fi lled with a fl uid are obtained from Gassmann equations. Results show that increasing the TOC volumes generally reduces both P-wave and S-wave velocities, acoustic impedance, and density. On the contrary, the vp/vs ratio increased as the impact of immature organic matter which will be more affecting shale rigidity than its compressibility.